Reducing variability in apparent operative inclination during total hip arthroplasty: findings of a randomised controlled trial. Issue 3 (May 2018) - O'Neill, Christopher K J; Hill, Janet C; Patterson, Christopher C; Molloy, Dennis O; Gill, Harinderjit S; Beverland, David E
Aims: To determine which of 3 methods of cup insertion most accurately achieved a target apparent operative inclination (AOI) of 35° ± 2.5°: (1) Freehand; (2) Modified Mechanical Alignment Guide (MAG); or (3) Digital Inclinometer assisted. Methods: Using a cementless cup via a posterior approach in lateral decubitus 270 participants were recruited, with 90 randomised to each method. The primary outcome was the unsigned deviation from target AOI. The digital inclinometer was used to measure AOI in all cases, though the surgeon remained blinded to the reading intraoperatively for both the Freehand and MAG methods. Results: Mean deviation from target AOI for the Freehand, Modified 35° MAG and Digital Inclinometer techniques was 2.9°, 1.8° and 1.3° respectively. When comparing mean deviation from target AOI, statistically significant differences between the Freehand / Inclinometer groups ( p < 0.001), the Freehand / Modified 35° MAG groups ( p < 0.001) and the Digital Inclinometer / Modified 35° MAG groups ( p < 0.023) were evident. The Digital Inclinometer technique enabled the surgeon to achieve a target AOI of 35° ± 2.5° in 88% of cases, compared to 71% of Modified 35° MAG cases and only 51% of Freehand cases. Discussion: The Digital Inclinometer and the Modified 35° MAG techniques were both more accurate than the Freehand technique, with the Digital Inclinometer technique proving most accurate overall. Radiographic inclination (RI) is also influenced by operative anteversion; however, the greatest source of error with respect to RI occurs when the pelvic sagittal plane is not horizontal at the time of acetabular component insertion. Clinical Trial Protocol number: NCT01831401